“A Sharp Offensive in all Directions:” The Canadian Labour Defense League and the Fight against Section 98, 1931–1936 - Eaton, C. Scott (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2018)
In 1931, eight leaders of the Communist Party of Canada (cpc) were convicted under Section 98 – a federal law that criminalized the advocacy of radical politics – and the party was declared illegal in Canada. The Canadian Labour Defense League (cldl), the party's ancillary organization responsible for legal matters, conducted an intense campaign directed at securing both the release of the party's leaders and the repeal of Section 98. This campaign included the distribution of pamphlets, the organization of demonstrations, and even the production of a dramatic play, entitled Eight Men Speak. Canadian state officials, led by Prime Minister R. B. Bennett, responded to the party's efforts oppressively. Prison guards fired shots into cpc general secretary Tim Buck's cell in Kingston Penitentiary, and Bennett himself had Eight Men Speak banned from performance in Toronto. Such kneejerk reactions, however, afforded cldl leaders opportunities to conduct meaningful work. This article argues that the cldl skillfully accentuated its own repression, keeping Section 98 relevant to Canada's voting populace and placing capitalism and the Canadian state on trial in the eyes of the Canadian public.